2012
DOI: 10.1007/s12017-012-8201-2
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Levels of Circulating Adiponectin in Mild Cognitive Impairment and Alzheimer’s Disease

Abstract: Adiponectin, an adipocytokine released by the adipose tissue and has important roles in the metabolic regulation and inflammatory control, may play an important roles in the physiopathology of psychiatric and neurodegenerative disorders. The aim of the present work was to evaluate adiponectin serum levels in patients with mild cognitive impairment (MCI) and Alzheimer's disease (AD) as compared to cognitively healthy elders and to correlate these levels with clinical and cognitive parameters. We further evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(102 citation statements)
references
References 37 publications
7
95
0
Order By: Relevance
“…Consistent with previous studies [7][8][9][10], serum APN levels in MCI and AD were significantly higher than in controls. A large-scale study in 2012 showed that increased plasma APN was an independent risk factor for development of all-cause dementia and AD in women [7].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous studies [7][8][9][10], serum APN levels in MCI and AD were significantly higher than in controls. A large-scale study in 2012 showed that increased plasma APN was an independent risk factor for development of all-cause dementia and AD in women [7].…”
Section: Discussionsupporting
confidence: 92%
“…Previous clinical studies have shown that lifestyle-related diseases such as hypertension, type II diabetes, dyslipidemia, and obesity may enhance the risks for AD and other neurodegenerative diseases [7][8][9][10]. However, only one study has examined APN in this context, with Une et al finding increased serum APN in patients with mild cognitive impairment (MCI) and AD compared to age-matched normal controls (NC) and increased CSF APN in MCI compared to NC [8].…”
Section: Introductionmentioning
confidence: 99%
“…(Table 1). 36 The reasons for the discrepancies among these studies are unclear, but the APN level may be affected by multiple factors. Given that many AD patients have concomitant metabolic disorders,1 it is possible that plasma APN may fluctuate during coprogression of the disease 37.…”
Section: Apn May Increase Ad Riskmentioning
confidence: 99%
“…In our point of view, it could also translate a protective effort against a neurotoxic insult. More recently, Teixeira et al (2013) demonstrated that circulating adiponectin levels were reduced in MCI and AD patients but did not predict progression to dementia. On other hand, Bigalke et al (2011) and Warren et al (2012) failed to demonstrate a correlation between plasmatic levels of this adipocytokine and AD.…”
Section: Adiponectinmentioning
confidence: 99%